A simple method to determine mating type in Neurospora discreta - Keyur K Adhvaryu; Shahana Sultana; Swathi SundarRaj; Ramesh Maheshwari (Fungal Genetics Reports, 2001)
In order to circumvent the problem in assigning the mating types of some N. discreta strains by fluffy testers, a PCR based method was developed. Between the two reference N. discreta strains (FGSC 3228 A and FGSC 4378 a), we observed the false perithecia to be more abundant in the "a" mating type. When we analyzed the octads from a cross of these two, the "false perithecia" appear to be associated with a particular morphology and mating type.